PENGEMBANGAN PRODUK AROMATERAPI BERBAHAN MINYAK ATSIRI KUNYIT SEBAGAI KOMODITAS UNGGULAN MASYARAKAT DESA BANDAR KABUPATEN PACITAN - Anif Nur Artanti; Fea Prihapsara; Hartatik Hartatik (Jurnal Abdi Insani, 2022)
Suroloyo Farmer Group I Bandar Village, Pacitan has been able to distill turmeric essential oil. So far, the turmeric essential oil produced is sold to essential oil suppliers. However, the benefits obtained are not commensurate with the energy and time spent. This activity aims to develop diversification of products made from turmeric essential oil into aromatherapy oil products that have high added value. This activity was divided into two stages, the first stage was training on the formulation of aromatherapy topical oil containing turmeric essential oil which was carried out at the Suroloyo Farmer Group I, Bandar Village, Pacitan. The second stage is the manufacture of aromatherapy topical oil containing turmeric essential oil in the Small Traditional Medicine Business CV. PJ. Ching Lung, Sukoharjo. This activity produces aromatherapy products containing turmeric essential oil. Turmeric essential oil is then formulated with fennel oil, eucalyptus oil and Lawang oil to become an aromatherapy topical oil product, which is packaged in a 10 ml roll-on dark glass bottle and labeled with the Ellevacare Oil® brand. This product has been registered for a distribution permit with the POM Agency and obtained a distribution permit number, namely TR213678301. This aromatherapy oil product is sold at a price of Rp. 15,000/bottle. The diversification of turmeric essential oil products can become a new business commodity in the Suroloyo Farmer Group I and increase production capacity at CV PJ Ching Lung. Coordination of the two partners is carried out on an ongoing basis based on the needs of the community which can be directly felt by the benefits.